High Activation of γδ T Cells and the γδ2pos T-Cell Subset Is Associated With the Onset of Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome, ANRS 12153 CAPRI NK - Pean, Polidy; Nouhin, Janin; Ratana, Meng; Madec, Yoann; Borand, Laurence; Marcy, Olivier; Laureillard, Didier; Fernandez, Marcelo; Barré-Sinoussi, Françoise; Weiss, Laurence; Scott-Algara, Daniel (Frontiers in Immunology, 2019)
Background: HIV-1 and M. tuberculosis co-infected patients are commonly at risk of immune reconstitution inflammatory syndrome (IRIS) when initiating antiretroviral treatment (ART). Evidence indicates that innate immunity plays a role in TB-IRIS. Here, we evaluated the phenotype of γδ T cells and invariant NKT cells in tuberculosis-associated IRIS. Methods: Forty-eight HIV+/TB+ patients (21 IRIS) and three control groups: HIV-/TB- (HD, n=11), HIV+/TB- (n=26), and HIV-/TB+ (n=22) were studied. Samples were taken at ART initiation (week 2 of anti-tuberculosis treatment) and at the diagnosis of IRIS for HIV+/TB+; before ART for HIV+/TB-, and at week 2 of anti-tuberculosis treatment for HIV-/TB+ patients. The γδ T cells and iNKT cells were analyzed by flow cytometry. Results: Before ART, IRIS and non-IRIS patients showed a similar proportion of γδ T and iNKT cells. HLA-DR on γδ T cells and γδ2pos T cells was significantly higher in IRIS than non-IRIS patients and controls (p<0.0001). NKG2D expression was lower in HIV+/TB+ patients than controls. CD158a expression on γδ T cells was higher in IRIS than non-IRIS (p=0.02), HIV+/TB-, and HIV-/TB- patients. Conclusion: The higher activation of γδpos T cells and the γδ2pos T cell subset suggests that γδpos T cells may play a role in the pathogenesis of IRIS.